Characterization of the 55-kb mouse histone gene cluster on chromosome 3. - Wang, Z F; Tisovec, R; Debry, R W; Frey, M R; Matera, A G; Marzluff, W F

(untitled) (Genome Research, 1996)
The histone gene cluster on mouse chromosome 3 has been isolated as a series of overlapping P1 clones, covering 110-120 kb, by probing with the histone H3-614 gene that had been mapped previously to mouse chromosome 3. There are genes for 10 core histone proteins present in a 55-kb cluster within this contig. There are three histone H3 genes, two of which are identical; four histone H2a genes, two of which are identical, one histone H4 gene; and two histone H2b genes. These histone H3 and H2a genes encode approximately 40% of the total H3 and H2a mRNA, whereas the histone H4 and histone H2b genes encode < 10% of the total H4 and H2b mRNA. There are no histone H1 genes present in this cluster. All of the histone H2a genes encode histone H2a.2 proteins (or variants of H2a.2), and account for all the H2a.2 genes in the mouse genome. All three histone H3 genes encode the histone H3.2 protein. A 21-kb region containing the adjacent H3-614 and H2a-614 genes has been duplicated and is present in an inverted repeat separated by 4.5 kb. The other two H2a genes are adjacent, with the 3' ends of their mRNAs separated by only 49 nucleotides in the DNA and the U7 snRNP binding sites separated by only 20 nucleotides. One of the histone H2b genes has lost the stem-loop sequence characteristic of the replication-dependent histone mRNAs and encodes only polyadenylated mRNAs.